Entomotherapeutic Role of Periplaneta americana Extract in Alleviating Aluminum Oxide Nanoparticles-Induced Testicular Oxidative Impairment in Migratory Locusts (Locusta migratoria) as an Ecotoxicological Model - Esraa A. Arafat; Doaa S. El-Sayed; Hussein K. Hussein; Justin Flaven-Pouchon; Bernard Moussian; Lamia M. El-Samad; Abeer El Wakil; Mohamed A. Hassan (MDPI AG, 2023)
In this study, we shed light for the first time on the usage of migratory locusts (Locusta migratoria) as an insect model to investigate the nanotoxicological influence of aluminum oxide (Al2O3) nanoparticles at low doses on testes, and evaluate the capacity of a whole-body extract of American cockroaches (Periplaneta americana) (PAE) to attenuate Al2O3 NPs-induced toxicity. Energy dispersive X-ray microanalyzer (EDX) analysis verified the bioaccumulation of Al in testicular tissues due to its liberation from Al2O3 NPs, implying their penetration into the blood-testis barrier. Remarkably, toxicity with Al engendered disorders of antioxidant and stress biomarkers associated with substantial DNA damage and cell apoptosis. Furthermore, histopathological and ultrastructural analyses manifested significant aberrations in the testicular tissues from the group exposed to Al2O3 NPs, indicating the overproduction of reactive oxygen species (ROS). Molecular docking analysis emphasized the antioxidant capacity of some compounds derived from PAE. Thus, pretreatment with PAE counteracted the detrimental effects of Al in the testes, revealing antioxidant properties and thwarting DNA impairment and cell apoptosis. Moreover, histological and ultrastructural examinations revealed no anomalies in the testes. Overall, these findings substantiate the potential applications of PAE in preventing the testicular impairment of L. migratoria and the conceivable utilization of locusts for nanotoxicology studies.